Power of Power To Sell as Collateral Confiscation In Debt Repayment Based on The Debt Recognition Deed - Tia Tasia Zein; Iman Jauhari; Siti Rahmah (Asian Journal of Social and Humanities, 2024)
The purpose of this study is to determine the power of power to sell as collateral confiscation in debt repayment based on the debt recognition deedDeed of Debt Recognition is a deed made by a notary in the form of a Grosse Deed containing the irah-irah "For Justice Based on the One and Only God" which means it has the same executory power as the Court Decision. However, in practice the Deed of Debt Recognition is made followed by the preparation of the Deed of Power of Attorney to Sell as a new deed, even though one form of legal protection outside of the guarantee institution is the making of the Grosse Deed of Debt Recognition. Thus, it is interesting to study further why the use of the power to sell is used as a guarantee for debt repayment under the Deed of Debt Recognition is more desirable and how the form of legal protection for debtors defaults and settlement of disputes arising from the Deed of Power to Sell. This research uses normative legal research types and qualitative methods. The result of the study is that the parties prefer to use the Power of Attorney to Sell because it does not go through a long procedure, does not take time and does not incur more costs. The legal protection obtained by the defaulting debtor is to obtain the remaining proceeds from the sale of collateral and the selling price of the collateral which must not be below the value of the collateral that should be, and the creditor must not have a collateral object if the debtor defaults.